2017
DOI: 10.4018/ijsds.2017100102
|View full text |Cite
|
Sign up to set email alerts
|

Variation Sharing

Abstract: The most fundamental problem currently associated with structural equation modeling employing the partial least squares method is that it does not properly account for measurement error, which often leads to path coefficient estimates that asymptotically converge to values of lower magnitude than the true values. This attenuation phenomenon affects applications in the field of business data analytics; and is in fact a characteristic of composite-based models in general, where latent variables are modeled as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Additionally, in order to ensure the robustness of the results, the model was assessed for endogeneity using the instrumental variable as recommended by Kock (2020). Kock and Sexton (2017) suggest conducting such an analysis using the single stochastic variation sharing method. The result of the analysis conducted showed that the link from the instrumental variable to the dependent variable was non-significant ( p -value = 0.143, β = −0.081).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Additionally, in order to ensure the robustness of the results, the model was assessed for endogeneity using the instrumental variable as recommended by Kock (2020). Kock and Sexton (2017) suggest conducting such an analysis using the single stochastic variation sharing method. The result of the analysis conducted showed that the link from the instrumental variable to the dependent variable was non-significant ( p -value = 0.143, β = −0.081).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…IV selectively shares variability with another variable. Utilizing the "Explore analytic composites and instrumental variables" menu in WarpPLS 8.0 with the "Single stochastic variation sharing" sub-option facilitates the creation and testing of IV for endogeneity control (Kock and Sexton, 2017). If the IV-link's path coefficient to the dependent variable is small and nonsignificant, it indicates successful implementation of the Heckman procedure, signifying no significant endogeneity in the model (Certo et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…To test the robustness of our structural model results, we relaxed the covariance-based structural equation modeling assumption of multivariate normality (Kock and Sexton, 2017). We used the factor-based PLS Type CFM3 algorithm in WARP PLS 8.0 to perform this procedure, which enables the modeling of non-linear relationships using both compositebased and factor-based SEM algorithms (Memon et al, 2021) and estimates a measurement model (Kock, 2022b).…”
Section: Robustness and Endogeneity Checksmentioning
confidence: 99%